Intimacy and Celebrity in Eighteenth-Century Literary Culture Public Interiors (Springer International Publishing, 2018)
This book provides an expansive view of celebrity's intimate dimensions. In the process, it offers a timely reassessment of how notions of private and public were negotiated by writers, readers, actors and audiences in the early to mid-eighteenth century. The essays assembled here explore the lives of a wide range of figures: actors and actresses, but also politicians, churchmen, authors and rogues; some who courted celebrity openly and others who seemed to achieve it almost inadvertently. At a time when the topic of celebrity's origins is attracting unprecedented scholarly attention, this collection is an important, pioneering resource.